2011
DOI: 10.1128/aac.01469-10
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial Activity of Modithromycin, a Novel 6,11-Bridged Bicyclolide, against Respiratory Pathogens, Including Macrolide-Resistant Gram-Positive Cocci

Abstract: The in vitro activities of modithromycin against Gram-positive and -negative respiratory pathogens, including macrolide-resistant cocci with different resistance mechanisms, were compared with those of other macrolide and ketolide agents. MICs were determined by the broth microdilution method. All 595 test strains used in this study were isolated from Japanese medical facilities. The erm (ribosome methylase) and/or mef (efflux pump) gene, which correlated with resistance to erythromycin as well as clarithromyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…In vitro activities similar to those of RBx 14255 were reported for cethromycin (ABT-773), another ketolide, and telithromycin against many resistant phenotypes, including activity against penicillin and macrolide-resistant Gram-positive bacteria (29). In a study by Sato et al (30), modithromycin (EDP-420, EP-013420, S-013420), a novel 6,11- pneumoniae, and the in vitro activities were comparable to those of our fluoroketolide, RBx 14255. Solithromycin is currently being developed in phase 3 clinical trials at Cempra, Inc., for the oncedaily oral treatment of mild to moderate community-acquired bacterial pneumonia (CABP), and phase 2 clinical trial results were recently reported (21).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro activities similar to those of RBx 14255 were reported for cethromycin (ABT-773), another ketolide, and telithromycin against many resistant phenotypes, including activity against penicillin and macrolide-resistant Gram-positive bacteria (29). In a study by Sato et al (30), modithromycin (EDP-420, EP-013420, S-013420), a novel 6,11- pneumoniae, and the in vitro activities were comparable to those of our fluoroketolide, RBx 14255. Solithromycin is currently being developed in phase 3 clinical trials at Cempra, Inc., for the oncedaily oral treatment of mild to moderate community-acquired bacterial pneumonia (CABP), and phase 2 clinical trial results were recently reported (21).…”
Section: Discussionmentioning
confidence: 99%
“…There are several molecular mechanisms by which bacteria, including P. aeruginosa, resist the action of macrolide, including target site modification by methylation and/or mutation that prevents the binding of antibiotics to their target molecules and inactivation of the drugs or efflux (23)(24)(25).…”
mentioning
confidence: 99%
“…The so-called bicyclolides introduce a second heterocycle between the 6 and 11 or 6 and 3 positions (73, 74). The 6, 11-bicyclolide modithromycin (Figure 1) exhibits improved in vitro efficacy against erm + strains of S. pyogenes showing idiosyncratic resistance to telithromycin (75). Another area of development unrelated to resistance is the alteration of the alkyl-arm to one containing an azetidine (azetidinyl ketolides in Figure 1).…”
Section: Structural Basis Of Resistance To Ptc-targeted Antibioticsmentioning
confidence: 99%